Carotid artery stenting without post-stenting balloon dilatation. (7th September 2013) - Ogata, Atsushi; Sonobe, Makoto; Kato, Noriyuki; Yamazaki, Tomosato; Kasuya, Hiromichi; Ikeda, Go; Miki, Shunichiro; Matsushima, Toshio
Abstract : Purpose: To evaluate the clinical outcome and MRI findings after carotid artery stenting (CAS) without post-dilatation. Methods: Between May 2005 and April 2012, a total of 169 consecutive patients (61.4% symptomatic) underwent 176 CAS procedures performed with an embolic protection device (GuardWire, n=116; FilterWire EZ, n=60). All stents were deployed without post-dilatation. Periprocedural complications and mid-term outcomes were analyzed. Results: The stroke rate was 2.3% within 30 days post-CAS (asymptomatic patients 1.5%; symptomatic patients 2.8%). Cerebral infarction occurred in one asymptomatic patient (1.5%) and one symptomatic patient (0.9%). Intracranial hemorrhage occurred in two symptomatic patients (1.9%). Post-CAS diffusion-weighted imaging (DWI) revealed a high-intensity area in 26 of 176 procedures (14.8%). Ipsilateral stroke after 31 days occurred in two patients (1.1%) and restenosis occurred in six (3.4%). A post-CAS comparison of the embolic protection devices revealed no difference in stroke incidence within 30 days and in DWI high-intensity area. Conclusions: Our CAS procedure without post-dilatation is feasible, safe and associated with a low incidence of stroke and restenosis.